Prognosis of biological activity and lipophilicity of some pyridine derivatives as components of anti-caries agents - V. O. Gelmboldt; I. V. Lytvynchuk; I. O. Shyshkin; L. N. Ognichenko; V. E. Kuz'min (The State Expert Center of the Ministry of Health of Ukraine, 2020)
In recent years, a high carioprophylactic efficacy of ammonium hexafluorosilicates with biologically active cations has been discovered (АHBC). In the case of using AHBC, there is a potential possibility of enhancing the anticaries effect of the fluorine-containing anion as a result of the contribution of the effects of cations, for example, anti-inflammatory effects. The purpose of the work is a virtual analysis of the biological activity and lipophilicity of pyridine derivatives containing pharmacophores associated with anti-inflammatory activity (AIA), as possible candidates for the synthesis of AHBC as anticaries agents. Objects of research are the commercially available pyridine derivatives (PubChem database) containing pharmacophore groups - residues of acetic, propionic, phenylacetic acids, the presence of which is associated with the manifestation of AIA. Assessment of the potential biological activity of the compounds was carried out using the program. PASS 2017 Professional. The lipophilicity values of logP pyridines were calculated using software packages ALOGPS, KowWin, model QSPR. It has been established that in the series of acetic acid derivatives the highest probability of the presence of AIA (Ра) is expected for isomeric pyridine acetic acids: there is a relative increase in the values of Pa in the series of 2-, 3-, 4-isomers (Ра = 0,454, 0,506, 0,537 respectively). The introduction of the second substituent into the pyridine ring (fluorine, bromine, chlorine atoms, CF3 group) is accompanied by a decrease in the values Ра. In the rows of 2-, 3-, 4-substituted derivatives of phenylacetic and propionic acids, an increase in the likelihood of AIA manifestation is also recorded; the introduction of substituents in the propionic acid residue (fluorine atoms, НО-, H2N-groups) leads to lower values Ра. For all studied derivatives, there was no significant probability of manifestation of hepatotoxicity and nephrotoxicity (Ра < 0,5), the calculated lipophilicity values of the compounds are in the range of -2,65‒2,26. Thus, all the studied pyridine derivatives correspond to Lipinsky's «rule 5» and can be classified as low toxic «drug-like» compounds. Despite the presence of pharmacophores in the pyridines, the presence of which is associated with AIA, for almost all structures the probability of the appearance of this type of activity is small (Ра ≤ 0,5). In our opinion, compounds with phenylacetic and propionic acids fragments are interesting as objects of further experimental research as the models for elucidating the influence of the position of the pharmacophore group in the structure of the pyridine ring on the value of the CPE and AIA of the corresponding AHBC.